PRODUKSI PROGRAM VARIETY SHOW “NGOPI” SEBAGAI MEDIA HIBURAN DAN EDUKASI DI TVRI BALI - Pande Putu Argyananta Artana; Ida Bagus Hari Kayana; Made Rai Budaya Bumiarta (CALACCITRA: JURNAL FILM DAN TELEVISI, 2026)
The NGOPI (Ngobrolin Orang Penuh Inspirasi) variety show is designed as an entertainment and educational program produced and broadcast via live streaming on the YouTube channel "Pande Argy". This research is a creation study (practice) using a descriptive-qualitative approach through production documentation, field observations, and post-broadcast evaluation. The production process includes pre-production (production book, rundown, PPM), production (live multicam), and post-production (evaluation & archiving). The results indicate success in building a warm and communicative segment format, but faced technical obstacles such as delayed broadcast starts and audio problems that affected the initial quality of the broadcast. Practical recommendations include increasing technical preparation time, strict audio checking protocols, and adding a short rehearsal before broadcast. This work contributes in the form of a practical guide for live streaming variety show production and learning materials for the development of similar programs.